GAMBARAN KUALITAS SARAPAN DAN STATUS GIZI SISWA SDN IBU JENAB 3 CIANJUR - authoria, Nila; Pratiwi1, Riska Y. Pratiwi1 Y; Permana, Dany; Pratiwi, Tiara F; Yunitaningrum, Utari (POLTEKKES KEMENKES MANADO, 2024)
Introduction: Breakfast for elementary school students is very important in supporting physical growth and improving learning achievement. Objective: This research is to determine the description of breakfast and nutritional status of grade 5 students at SDN Ibu Jenab 3 Cianjur. Method: This research is a descriptive study with a cross sectional design. This research was conducted in June 2024 with a sample size of 32 students from class 5 of SDN Ibu Jenab 3 Cianjur. Description of breakfast was obtained through interviews from questionnaires and nutritional status was obtained from anthropometric measurements. Results: This research showed that the behavior of students who did not miss breakfast was 84.4% and their nutritional status was in the good category, 62.5%. The quality of breakfast related to nutrition is in the poor category at 59.3%. Conclusion: In this study, the majority of students had good nutritional status, but the nutritional quality of students' breakfast was in the poor category. Key words: Breakfast quality, Nutritional status, Elementary school students.